2001
DOI: 10.1046/j.1460-2695.2001.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fatigue crack growth in titanium aluminides and hydrogen evolution behaviour

Abstract: The influence of environment on fatigue crack growth behaviour was investigated both in nearly lamellar and in duplex titanium aluminides, and the hydrogen evolution kinetics was analysed by thermal desorption spectroscopy. The tensile strength of the duplex material decreases in the order of the extent of the water molecule content in the environment: the strength in vacuum is the highest, and decreases in the order of laboratory air and finally in water. In the case of the lamellar material, the fatigue crac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
1
3
0
1
Order By: Relevance
“…[12][13][14][15][16] In these cases, hydrogen is introduced from test atmospheres, such as in a flowing hydrogen gas or in air, the moisture in which is suggested to be able to react with the alloy and to generate atomic hydrogen, resulting in reduced tensile elongation. Furthermore, similar results have been obtained under fatigue loading [17] or for polysynthetic texture (PST) TiAl crystals. [18,19] Fatigue crack growth rates were enhanced by moisture in the test environment.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…[12][13][14][15][16] In these cases, hydrogen is introduced from test atmospheres, such as in a flowing hydrogen gas or in air, the moisture in which is suggested to be able to react with the alloy and to generate atomic hydrogen, resulting in reduced tensile elongation. Furthermore, similar results have been obtained under fatigue loading [17] or for polysynthetic texture (PST) TiAl crystals. [18,19] Fatigue crack growth rates were enhanced by moisture in the test environment.…”
Section: Introductionsupporting
confidence: 79%
“…[18,19] Fatigue crack growth rates were enhanced by moisture in the test environment. [17] The tensile elongation of PST crystals with soft orientation deformed at room temperature was greatly dependent on the testing atmosphere, and was lower in air than in vacuum. [18,19] For the Ti-49 at.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated that contamination from the melting atmosphere might easily cause the deterioration of the mechanical properties in titanium castings since cp Ti and Ti-based alloys are very reactive at high temperatures [3]. The formation of intermetallic compounds, and substitutional and interstitial solid solutions under this condition leads to the formation of a fragile material [6], with low elongation. Among the drawbacks caused by the contamination of cp Ti and titanium-based alloys one can list the reduction in the fatigue limit and the elongation of clasps of removable partial denture frameworks [4].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the casting of commercially pure titanium (cp Ti) or titanium-based alloys for dental purposes, such as partial denture frameworks or certain single units can be very difficult [3,4]; indeed these alloys are considered one of the most difficult metals to process, mainly because they require high temperatures for melting, low castability, high chemical reactivity at high temperature with silica-based investments and the high affinity of titanium for some elements, such as oxygen, nitrogen and hydrogen as well as carbon. The latter dissolves interstitially [5], leading to increase in hardness and alloy embrittlement [6], and the high reactivity, particularly with the investment, induces the formation of the α-case layer [7]. This high chemical reactivity demands the use of specially formulated investment materials containing alumina, magnesia and calcia instead of silica-based investments.…”
Section: Introductionmentioning
confidence: 99%
“…O risco de realizar uma fundição de titânio em ambiente rico de impurezas, principalmente oxigênio, nitrogênio e hidrogênio, é o de poder provocar uma grande alteração nas propriedades e na composição do material, já que este metal apresenta alta reatividade em temperaturas acima de 600°C (VOITIK, 1991). Esta contaminação leva à obtenção de um material frágil, quebradiço e obviamente, de baixo alongamento, devido à formação de composto intermetálicos, soluções substitucionais e intersticiais (MINOSHIMA et al, 2001). Dentre os diversos transtornos causados por esta contaminação está a redução no limite de fadiga e alongamento de grampos e armações em peças de prótese parcial removível (VALLITTU;KOKKONEN, 1995).…”
Section: Discussionunclassified